1999
DOI: 10.1063/1.478678
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian basis sets for use in correlated molecular calculations. IX. The atoms gallium through krypton

Abstract: Valence correlation consistent and augmented correlation consistent basis sets have been determined for the third row, main group atoms gallium through krypton. The methodology, originally developed for the first row atoms, was first applied to the selenium atom, resulting in the expected natural groupings of correlation functions ͑although higher angular momentum functions tend to be relatively more important for the third row atoms as they were for the second row atoms͒. After testing the generality of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
766
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,360 publications
(792 citation statements)
references
References 54 publications
1
766
0
7
Order By: Relevance
“…This is due to the fact that the spread of Hamiltonian eigenvalues increases as larger basis sets are used. Thus, the fastest decay of ||D G1 || F is observed in cc-pVDZ [59] basis with 27 basis function and the slowest in the aug-cc-pVQZ [59] with 97 functions. Note that even when a basis with a pseudopotential that has only basis functions describing the valence orbitals is employed, to be in the linear regime requires more than 10,000 frequencies.…”
Section: The Frobenius Norm ||Dmentioning
confidence: 95%
“…This is due to the fact that the spread of Hamiltonian eigenvalues increases as larger basis sets are used. Thus, the fastest decay of ||D G1 || F is observed in cc-pVDZ [59] basis with 27 basis function and the slowest in the aug-cc-pVQZ [59] with 97 functions. Note that even when a basis with a pseudopotential that has only basis functions describing the valence orbitals is employed, to be in the linear regime requires more than 10,000 frequencies.…”
Section: The Frobenius Norm ||Dmentioning
confidence: 95%
“…Then, additional uncontracted functions are used to describe the electronic correlation, see the works of Dunning [45][46][47][48][49][50][51][52][53] as a representative example. We found that GTO basis sets designed according to this principle somewhat lack flexibility for the l = 0 partial wave, especially in the molecular environment, since the number of uncontracted 1s orbitals is typically small.…”
Section: Basis Setsmentioning
confidence: 99%
“…Since the seminal work of Dunning and co-workers [45][46][47][48][49][50][51][52][53] it has been known that to allow for a reliable extrapolation towards CBS, basis sets need to be constructed according to the correlation consistency principle. Roughly speaking, it ensures that at a given stage all functions which give approximately the same energy contributions are simultaneously included.…”
Section: Basis Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gas phase optimizations of all isomers of different [TeXnY6-n] 2-(X = Cl, Y = Br) anions were carried out using the PBE0 density functional [38][39][40][41] and correlation consistent basis sets of triple--valence quality (aug-cc-pVTZ for Cl and Br, and aug-cc-pVTZ-PP for Te) [42][43][44]. The program package [45].…”
Section: Computational Detailsmentioning
confidence: 99%